PENGGUNAAN METODE THINK PAIR SHARE DALAM MENINGKATKAN HASIL BELAJAR PPKn TENTANG KEBEBASAN BERORGANISASI PESERTA DIDIK KELAS V - Hidayanti, Wahyu (JURNAL SINEKTIK, 2020)
The purpose of this study was to describe the use of Think Pair Share (TPS) Method in PPKn learning and analyze the use of TPS method to improve PPKn learning outcomes about Freedom of Organization of Class V students of SDN Tlogomojo in Semester II of Lesson Year 2017/2018. The results of this study are 1) The use of Think Pair Share method in PPKn learning about Freedom of Organization begins with interactive and interesting opening activities, 2) The use of Think Pair Share method in PPKn learning is continued with group tasks with a number of questions comparable to the number of members, 3) The use of TPS PPKn method on Freedom of Organization with the same group composition, 4) The use of TPS method in PPKn increases the learning activities of learners in answering questions from teachers and friends, asking questions, and arguing to teachers, 5) The use of TPS methods improves ppkn learning outcomes on Freedom of Organization satisfactory with an average of 88.82 and completeness of 88.23%.